Annual Development Plan of Madhya Pradesh 1957-58 - Planning Commission (Planning Commission, 1957)
For a proper appreciation of the Second Plan and the annual plan for the second year, which is the subject matter of this publication, it is necessary to view the basic statistics of the new State and its economy. Madhya Pradesh is the second biggest State in the country (Bombay coming first) from the point of area which is 1,71,000 sq. miles. The population of the State is 261 lakhs of which 204 lakhs or 78 per cent of the total population depends upon agriculture. The net area sown in 1954-55 was 382 lakh acres but the area under irrigation was only 21 lakh acres which works out to 5.49 per cent of the total area shown as against the all-India percentage of 17 per cent. The average yield per acre of different crops is generally low as compared to other States. The State has a total population of 35 lakhs scheduled castes and 39 lakhs scheduled tribes. The percentage of scheduled castes is 13.41 while that of scheduled tribes is 14.94. The percentage of both scheduled castes and scheduled tribes to the total population is 28.35 Per cent. The total mileage of roads in the State at the commencement of the Second Plan was 17,608 which works out 0.10 miles per sq. mile and one mile of road served 1,482 persons.
Government of Madhya Pradesh, Planning and Development Department